PENGARUH TEMAN SEBAYA TERHADAP MINAT SISWA SMP NEGERI MEMILIH KOMPETENSI KEAHLIAN TATA KECANTIKAN PADA SMK NEGERI 3 PAYAKUMBUH - Widiatuti, Amelia; Rahmiati, Rahmiati; Hayatunnufus, Hayatunnufus (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This research the first time from the low interest of SMP student to SMK. The purpose from this research to describe about the effect of the same age to interet SMP student for choice the skill competence beautymaking at SMK N 3 Payakumbuh. The type of this research is quantitative with correlation descriptive. This research population students of class IX SMPN 3 Payakumbuh, SMPN 5 Payakumbuh, SMPN 8 Payakumbuh and SMPN 9 Payakumbuh which amounted to 659 students. The extraction technique sample with random sampling by having 73 students as the sample. The research of data is primer data from respondent questioner for 50 items questions with likert scale. Data analysis technique is descriptive analysis, inferential analysis test, simple regression and hypothesis test (uji t) with SPSS versi 16.0 program. Based on the research result is the same age influence to interet SMP student for choice the skill competence beautymaking at SMK N 3 Payakumbuh which amounted to 75,1% and 24,9% influence with another variabel is not be able in this research. Key word : The Same Age, Interest, Skill Competence Beautymaking.